Percepção do professor acerca da trajetória da construção do projeto pedagógico 2010-2012 do curso de graduação em enfermagem da Universidade Federal de São Paulo - Magalhaes, Solange Maria Fustinoni [UNIFESP] (2016)
The aim was to show teachers perception on the Pedagogical Project building process of the Nursing Graduation at Escola Paulista de Enfermagem at Universidade Federal de São Paulo, in the period from 2010 to 2012, identifying the social, political and ethical principles that mobilized them during this process, how they operated internal negotiations e how these were perceived by them. A qualitative study was done, in the Thematic Oral History modality. For that purpose, six teachers narratives were collected. These teachers have participated in, at least, half of the meetings accomplished to the Pedagogical Project construction through semi-structured interviews. The narratives were recorded, transcribed, transcreated and analyzed, respecting all method stages and ethical precepts. Pierre Bourdieu?s social world theory was used as a theoretical and philosophical reference for analysis. Three thematic categories were built based on thematic clustering of excerpts from narratives by similarity and pertinence. The first was ?Vision on Pedagogic Project?, which sought to present the concept of Pedagogic Project brought by the teachers in their narratives and the recognition of the need of changes in the paradigms existing at EPE regarding to this concept. The second category, ?Operationalization of EPE Pedagogical Project building?, was focused on the negotiation process to the construction of the Pedagogic Project, the principles assigned to it by engaged actors, existing conflicts, power relations among them and how decisions were implemented. In third category, ?Identity of the Curriculum of Escola Paulista de Enfermagem? the curriculum concept and its role in the EPE nurse education was discussed. The conclusion was that, during EPE Pedagogic Project building, it was evident a concern about nurse education beyond knowledge accumulation, relating theory to practice, and form and substance, to surpass technical rationale logic and move towards being a professional supported by acquired and elaborated knowledge. It was also evident that teacher?s pedagogic practice is a consequence of a given context and a professional habitus, which is not reflexive or conscious, tending to the reproduction of this professional habitus and hampering the changes in teaching practice. So, it is necessary to rethink teaching strategies and pedagogic theoretical references to be used and to foster debates and analysis on teachers and students role with social actors of the teaching-learning process to graduate, effectively, questioning and reflexive professionals.